ANALYSIS OF THE LEVEL OF WORK LOYALTY OF SAFF AND EMPLOYEES THROUGH JOB SATISFACTION FACTORS AT THE PT. LSIP - Andry Roy; Abdul Gani; Emilia Embun Sari; Ayu Wirda Ningsih (Jurnal Ekonomi, 2023)
The development of economic needs today greatly affects the state of workers, so every company must continuously maintain the level of job satisfaction and work loyalty of its employees. This needs to be done to be able to ensure that the company can develop and achieve the goals that have been set. Organizational resources can be broadly divided into two groups, namely: human resources and non-human resources. Human resources include all people who have the status of members in the organization, each of which has a role and function. Human resources are human potentials inherent in a person which include physical and non-physical potentials.